The Influence of Eco-Influencers and Social Media Advocacy on Purchase Intentions for Eco-Friendly Products in West Java - Arief Fahmi Lubis; Paramita Andiani; Salwa Aulia Novitasari (West Science Interdisciplinary Studies, 2026)
The increasing environmental awareness among consumers has encouraged businesses to promote eco-friendly products through digital communication channels. Social media has emerged as a powerful platform for influencing consumer behavior, particularly through eco-influencers and environmental advocacy campaigns. This study aims to examine the influence of eco-influencers and social media advocacy on consumers’ intention to purchase eco-friendly products in West Java. A quantitative research approach was employed using a survey method. Data were collected from 175 respondents who actively use social media and are familiar with eco-friendly products. The research instrument utilized a five-point Likert scale, and the collected data were analyzed using SPSS version 25 through validity testing, reliability testing, descriptive analysis, multiple linear regression, coefficient of determination analysis, and hypothesis testing. The results reveal that eco-influencers have a positive and significant effect on purchase intention, indicating that credible environmental influencers can effectively encourage consumers to consider eco-friendly products. Social media advocacy also demonstrates a positive and significant influence on purchase intention, suggesting that environmental campaigns disseminated through social media enhance awareness and motivate sustainable purchasing behavior. Furthermore, eco-influencers and social media advocacy simultaneously influence purchase intention, explaining 46.1% of the variance in consumers’ intention to purchase eco-friendly products. The findings highlight the strategic importance of digital environmental communication in promoting sustainable consumption and provide practical implications for businesses, marketers, and policymakers seeking to encourage environmentally responsible purchasing behavior.